Przemiany strukturalne w spółdzielniach kółek rolniczych w warunkach gospodarki rynkowej - Hybel, Jan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1998)
The paper composes outcomes of survey carried out on 77 agricultural society cooperatives across the whole country. An analysis has been conducted according to regions and covers years 1990-1996. Research results show that the in the period under study agricultural society cooperatives (SKRs) had problems with fulfilment of market economy requirements. These of them that still deal with traditional economic activity faced strong competition from private sector of services, and in result lost their financial liquidity. Since 1990 the assets as well as level of employment and size of economic activity in investigated SKRs have been constantly decreasing. Economic transition period was the most favourable for cooperatives dealing with following activities: trade, building, repair services, running gas stations and diagnostic stations, roads modernisation, and construction of sanitary (sewage) installations. These cooperatives derived profits and successfully managed with competition. Results from an empirical investigation suggest that same cooperatives are too weak in terms of economic efficiency and will collapse. On the other hand there exist chances and opportunities for effective, viable cooperatives for their further development. These cooperatives contribute both to extension of service market and labour market in rural regions.